The reliability and adaptive responses of gross efficiency in hot ambient conditions - Waldron, M. (International Journal of Sports Medicine, 2014)
This study evaluated the reliability and adaptive responses of cycling gross efficiency (GE) performed at different intensities, across 3 trials in simulated hot (~30°C) temperatures. Twelve cyclists performed 3 hot (30±0.7ºC and RH of 50±2.9%) GE sessions, comprising 3 sub-maximal work rates of 150W, 200W and 250W (5-min each), separated by 24-h. Paired t-tests revealed no changes (P>0.05) in GE between trials. 95% limits of agreement demonstrated random error in GE ranging from 1.71% (250W; trials 1-2) to 2.32% (200W; trials 1-2), leading to a total error of -2.45%. The coefficient of variation (CV%) ranged from 3.1±0.4% (250W; trials 1-2) to 4.0±0.5% (200?W; trials 1-2). Among non-acclimated, well-trained cyclists, GE did not change between consecutive submaximal cycling bouts performed in the heat. The reliability of GE when cycling in the heat (CV=3.1-4.0%) is similar to that reported among cyclists in thermoneutral environments. Whilst the interpretation of GE reliability was dependent on the adopted statistical technique, it can be small enough to detect typical changes owing to heat exposure.